2021
DOI: 10.1007/s00787-021-01883-7
|View full text |Cite
|
Sign up to set email alerts
|

Dual orexin receptor antagonists for insomnia in youth with neurodevelopmental disorders: a case series and review

Abstract: Insomnia is a common, impairing, and difficult-to-treat comorbidity in children with neurodevelopmental disorders (NDDs). Behavioral interventions can be challenging because of developmental and behavioral features that interfere with treatment. Medication management also can be difficult due to a high burden of side effects, a high rate of paradoxical responses, and frequent treatment resistance. Therefore, new treatment options for insomnia in children with NDDs are needed. Dual orexin receptor antagonists (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…This may reflect referral bias, as referred patients may have more acute symptoms, the potential treatment-refractory nature of the patient population, and/or the genetics expertise of neuropsychiatric providers with reciprocal collaboration with medical genetics. Many families reported reduced symptoms and improved functioning for complex neuropsychiatric disorders including improved stabilization of schizoaffective disorder in a patient with 22q11.2 deletion syndrome and resolution of treatment-refractory insomnia through suvorexant and quetiapine trials in a patient with Kleefstra Syndrome [29]. No pre- and post-standardized assessment of psychiatric symptoms or adaptive functioning were obtained, limiting our ability to objectively determine the clinical impact of medication adjustments using a genomics-informed approaches compared to treatment-as-usual.…”
Section: Discussionmentioning
confidence: 99%
“…This may reflect referral bias, as referred patients may have more acute symptoms, the potential treatment-refractory nature of the patient population, and/or the genetics expertise of neuropsychiatric providers with reciprocal collaboration with medical genetics. Many families reported reduced symptoms and improved functioning for complex neuropsychiatric disorders including improved stabilization of schizoaffective disorder in a patient with 22q11.2 deletion syndrome and resolution of treatment-refractory insomnia through suvorexant and quetiapine trials in a patient with Kleefstra Syndrome [29]. No pre- and post-standardized assessment of psychiatric symptoms or adaptive functioning were obtained, limiting our ability to objectively determine the clinical impact of medication adjustments using a genomics-informed approaches compared to treatment-as-usual.…”
Section: Discussionmentioning
confidence: 99%
“…A case study of one 16-year-old male with bipolar 1 disorder given a trial of suvorexant at 10 mg nightly observed successful resolution of insomnia, along with improved sleep duration and quality (Prieto et al, 2019). Lastly, a case series of three youth and one adult with neurodevelopmental disorders reported benefit from suvorexant for both the 14-yearold adolescent and the 28-year-old young adult, who experienced significant improvements in sleep initiation and maintenance (Besterman and Jeste, 2023). The 9 and 13-year-old girls, however, experienced no benefit nor significant side effects, and their medication was discontinued.…”
Section: Orexin Receptor Antagonistsmentioning
confidence: 97%
“…Orexin or hypocretin antagonists, three of which have been FDA approved for the treatment of insomnia in adults (suvorexant, lemborexant, and daridorexant), block hypothalamic orexin receptors that are important for arousal and wakefulness (Besterman and Jeste, 2023). There is limited data for their use in the pediatric population (Donskoy and Loghmanee, 2018).…”
Section: Orexin Receptor Antagonistsmentioning
confidence: 99%
“…Nevertheless, it indicates that suvorexant could be a viable treatment option for adolescents grappling with insomnia and conceivably ASD [59]. In a recent study of 3 children (2 with ASD) and 1 adult patient with neurodevelopmental disorders, has been reported one patient showed a strong improvement in sleep onset and maintenance, and another showed a significant improvement in insomnia symptoms in combination therapy with trazodone, and two patients have shown a slight benefit or no benefit from suvorexant treatment [60].…”
Section: Suvorexantmentioning
confidence: 99%